A wafer-scale 1 nm Ni(OH)2 nanosheet with superior electrocatalytic activity for the oxygen evolution reaction. Issue 11 (28th February 2018) - Tian, Peng; Yu, Yanhao; Yin, Xin; Wang, Xudong
Abstract : A wafer-scale 1.4 nm Ni(OH)2 nanosheet is fabricated by ionic layer epitaxy and shows orders of magnitude higher electrocatalytic mass activity for OER compared to typical OER catalysts. Abstract : A wafer-scale 1.4 nm ultrathin Ni(OH)2 nanosheet was synthesized by ionic layer epitaxy. This free-standing Ni(OH)2 nanosheet was directly used to catalyze the oxygen evolution reaction (OER). At a current density of 10 mA cm −2, the overpotential reached 295 mV ( vs. RHE) in Fe-rich 1 M NaOH. This 1.4 nm Ni(OH)2 nanosheet showed a very high turnover frequency of 5.47 s −1 and a mass activity of more than 2 × 10 4 A g −1 at an overpotential of 300 mV. Such a high electrocatalytic mass activity of the Ni(OH)2 nanosheet was more than 2 orders of magnitude higher than those of typical OER catalysts. The capability of producing wafer-scale nanometer-thick nanosheets offers a promising strategy to improve the mass efficiency of electrochemical catalysts, which is particularly valuable for preserving rare and precious catalyst materials.